Improving the Oxidative Stability of Sunflower Oil Through Supercritical Impregnation-Assisted Pla/Cinnamaldehyde Active Packaging - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A; Villegas-Vallejos, C (American Chemical Society, 2025)
In the present study, the supercritical impregnation process using carbon dioxide (scCO2) was applied to incorporate the active compound cinnamaldehyde into PLA films, aiming to develop an innovative active food packaging solution. This approach leverages the unique properties of scCO2 to achieve efficient incorporation of bioactive compounds. Impregnation tests were performed at a pressure of 12 MPa, a constant temperature of 40 °C, and a controlled depressurization rate of 1 MPa min-1, ensuring optimal conditions for the process. The impact of the active compound incorporation via this cutting-edge technique on the oxygen and water vapor barrier properties of the films was thoroughly evaluated, revealing critical insights into material performance. In addition, the release kinetics of cinnamaldehyde in different food simulants were analyzed, and the partition (KPLA/SS) and diffusion (DCi) coefficients were determined, providing a deeper understanding of compound migration behavior. The oxidative stability of sunflower oil under accelerated storage conditions was also assessed, demonstrating the efficacy of the impregnated films in preserving oil quality. Key findings include the observation that the impregnation process and the incorporation of cinnamaldehyde induced a notable decrease in barrier properties, attributed to the plasticizing effects of the active compound and scCO2. Furthermore, the highest release of cinnamaldehyde was observed in simulants with higher ethanol concentrations, emphasizing the interaction between the active films and food matrices. Finally, the impregnated films significantly enhanced the oxidative stability of sunflower oil, as evidenced by lower peroxide index values, conjugated dienes, and trienes compared to control samples. These results underscore the potential of supercritical impregnation as a sustainable and efficient technology for developing advanced active food packaging materials, offering improved functionality and extended shelf life for food products. © 2025 American Chemical Society.